Allah yang Kreatif dan Dinamis dalam Ayub 42:7-17: Sebuah Perlawanan terhadap Teologi Retribusi - Firman Panjaitan; Hendro Hariyanto Siburian (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2020)
Theology often places the discourse on suffering in the concept of retribution, in the sense that suffering can occur because humans oppose God. Therefore, the way of deliverance or solution to suffering is through repentance, steadfastness, and persistence in suffering. This theological model of retribution is very contradictory to the message conveyed in the book of Job. By using the method of narrative interpretation, which tries to divide Job's story into several episodes and draws a